Analisis Kesulitan Belajar Siswa Kelas II Pada Materi Penjumlahan Dan Pengurangan Bilangan Di SD Negeri 143 Palembang - Padli Sajadah; Patricia H.M Lubis; Arief Kuswidyanarko (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Education is a very important need, because education will give birth to intelligent generations to advance the nation. In the 2013 curriculum at the elementary school level, there is thematic learning, which is interpreted as learning designed based on certain themes which are viewed from various subjects. Students often have difficulty relating one subject to another. This research method is a qualitative method, the object of this research is analyzing students' learning difficulties in addition and subtraction material. The informants were the class teacher and class II students at SD Negeri 143 Palembang. This research uses data collection techniques, namely observation, questionnaires and math ability tests. Then, from the results obtained, data analysis was carried out by reducing the data and presenting the data and verifying the data. Based on the results obtained, the forms of student learning difficulties in adding and subtracting numbers, namely the lack of concept of addition or subtraction operations involving tens and hundreds, have not been fully mastered. Students' learning difficulties in addition and subtraction material are an important focus for teachers in providing effective learning and of course students can understand more easily.